Using domain ontologies for improved retrieval of e-learning materials - Mirasol, Anne Ivy G.
Due to the huge volume of content available in the Web and in e-learning sites and repositories, it is a challenge for teachers and students to find the resources they need. General-purpose web search engines that employ generalized , keyword-based algorithms leave much room for improvement for domain-specific searching due to their reliance on the presence or absence of the query terms within a document. Since these search engines cater to wide-ranging documents they are therefore not the most suitable in applying features specific to e-learning corpora. This thesis presents a retrieval system designed for Philippine e-learning resources. The retrieval system uses domain ontology to capture valuable background information on the resource. This ontological information, along with Learning Object Metadata (LOM)-prescribed metadata and the resources"actual contents, are used during the retrieval process to improve both precision and recall of the system. Initial test results on 709 materials comparing the performance of ontology-assisted retrieval versus regular keyword-based retrieval and database text searching indicate that the ontology-assisted approach implemented showed improved retrieval of materials for our target domain.